2020
DOI: 10.1039/d0sm00766h
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling the pinning force of liquid droplets on liquid infused surfaces

Abstract: Liquid infused surfaces with partially wetting lubricants have recently been exploited for numerous intriguing applications. Here, we study the factors that control the pinning force and the contact angle hysteresis of liquid droplets on liquid infused surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The droplet starts to slide when the external body force is larger than the pinning force that holds the droplet on the surface. The pinning force for a droplet on the liquid-infused surface is given by the formula where and are the density and volume of the droplet, is the maximum angle of the droplet staying pinned, and is the gravitational acceleration ( 34 ). The maximum angle of the pinned droplet, , has the following relation to the lubricant–droplet contact angle, , and to the areal fraction of the soft pillars over the whole lubricated surface, : .…”
Section: Resultsmentioning
confidence: 99%
“…The droplet starts to slide when the external body force is larger than the pinning force that holds the droplet on the surface. The pinning force for a droplet on the liquid-infused surface is given by the formula where and are the density and volume of the droplet, is the maximum angle of the droplet staying pinned, and is the gravitational acceleration ( 34 ). The maximum angle of the pinned droplet, , has the following relation to the lubricant–droplet contact angle, , and to the areal fraction of the soft pillars over the whole lubricated surface, : .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4a, measuring the water CA of different lattice surfaces using the sessile drop method, the volume of the water droplet was 5, 6, and 7 μL. According to the method in the literature, 26 the radius of the solid−liquid contact interface R d is given the following equation…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As shown in Figure a, measuring the water CA of different lattice surfaces using the sessile drop method, the volume of the water droplet was 5, 6, and 7 μL. According to the method in the literature, the radius of the solid–liquid contact interface R d is given the following equation where V is the droplet volume and θ is the CA. The calculation showed that the average solid–liquid contact interface radii of 5 and 6 μL droplets were 550.7 and 587.6 μm, respectively, which were both smaller than the lattice structure radius of 600 μm.…”
Section: Resultsmentioning
confidence: 99%
“…As the slope of the protrusion increases, the pinning force of the droplet on the surface decreases, resulting in a decrease in the CA hysteresis, which eases the rolling of the droplets. [27,28] 3.3. Analysis of the Self-Assembly Modification Mechanism of the Microstructure Surface…”
Section: Surface Wettability Analysismentioning
confidence: 99%